DAMPAK PENGGUNAAN MEDIA SOSIAL INSTAGRAM DALAM GAYA HIDUP SISWA SMK AL-QUR’AN DAN DAKWAH ALAM DI KRINCING - Afrianto, Andri; Muryati, Sri; Hadi, Agustinus Sutriyanto (Journal of Democratia, 2024)
Social Media is an online media that allows humans to interact with each other without being limited by distance, space and time. This study takes the title Impact of Social Media Use on the Lifestyle of ADA Krincing Vocational High School Students with the aim of knowing the impact of using social media on student lifestyles and to find out efforts to overcome the negative impact of using social media on the lifestyle of ADA Vocational High School students. This research is a qualitative research and data collection techniques used are observation, interviews and documentation. In conducting data analysis, researchers used data analysis techniques proposed by Miles and Huberman, where each component includes data reduction, data presentation, and drawing conclusions. These findings lead to the conclusion that not all Islamic boarding school youth experience the impact of using social medi a on their lifestyle. Then, respond to these impacts holistically and overcome them. There are three impacts of using social media on lifestyle, namely clothing, finances, and leisure time. Some efforts to prevent negative impacts on students' lifestyles on social media, although these efforts do not spontaneously overcome these negative impacts entirely, are by means of: Conducting discussions in spare time, Quality Time with friends, Providing Additional Education, and Controlling Media Use social.